Production of steel-concrete composite columns for blast tests - Adam Čítek; Karel Hurtig; Martin Kryštov; Vojtěch Šulc; Marek Foglar; David Čítek (Acta Polytechnica CTU Proceedings)
The resistance of structures to explosive impacts is a highly relevant issue in modern engineering. During an explosion, structures are subjected to extreme dynamic loads, which necessitate advanced materials and reinforcement strategies. UHPFRC, with its evenly distributed steel fibres, exhibits exceptional mechanical properties that make it well-suited for blast-resistant applications. Combining UHPFRC with steel reinforcement is expected to significantly mitigate structural damage under explosive loading. This article focuses on the process of production of testing steel-concrete column specimens under axial compressive load for evaluating their blast resistance. The initial section describes the test elements and the objectives of the experiment. The following section outlines the design and material properties of the concrete mixtures used. Subsequently, the production process, including formwork preparation and casting, is detailed. Finally, the results achieved from ongoing testing are briefly introduced.